Clear-water scour at submerged pile groups. Issue 1 (2nd January 2019) - Galan, Alvaro; Simarro, Gonzalo; Fael, Cristina; Cardoso, Antonio H.
ABSTRACT: Accurate estimates of the scour depth around submerged pile groups are important in river engineering for a number of reasons, however, the literature on this issue is scarce. This study introduced an experimental campaign of 48 long-duration clear water experiments at submerged and skewed pile groups composed of cylindrical elements under steady flow. The effects of the skew angle, submergence ratio and pile group configuration on the equilibrium scour depth were investigated. The experimental scour depths were compared with the results from the HEC-18 empirical method and a modification of it to take into account a wide range of submergence ratios was proposed. Further, a new formulation to estimate the equilibrium scour depth at submerged pile groups was introduced with good agreement for the tests under consideration. Some considerations about the most employed characteristic lengths used to normalize the equilibrium scour depth were made.